Origination, turning point and key points of Chinese sports development - Gao, X. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The Chinese sports development outlook originated from the sports instrumental theory and has influenced the Chinese sports system, originations and operation mechanism. Additionally, it has influenced the sports talent selection and sports profits. While sports development based on the instrumental theory has helped to improve the national physique and promotion of the national position, it has resulted in the population making numerous sacrifices. With the enhancement of the national economy and the people`s heightened awareness of the value of sport, there has been an increased need for sport in various forms. It should be acknowledged that sports development based on the instrumental theory cannot reflect the nature of sports, when human beings are used as instruments for sports. Therefore, it is necessary that the Chinese sports development should be centered on the humanistic theory as opposed to the instrumental theory. Methods Literature review; expert interview; social investigation. Results The Chinese sports development theory should change from the instrumental theory to the humanistic theory. Human beings should be at the centre of sports development, systems and administration. Conclusions 1. The basic outlook for Chinese sports development is the instrumental sports development outlook, used to satisfy the national benefits under the planned economy. 2. In China the population is more concerned about the improvement of their health and quality of life. Sports and fitness have become an indispensable part of the people`s life. The Beijing Olympic Games will be the turning point for the development of Chinese sports. 3. In the future, Chinese sports development should focus on the humanistic theory. The approach will ensure sports development strategies can be altered and the humanistic idea can be applied in the construction of the sports system, policies and regulations, personnel